Colour opponency: Chromatic and achromatic circuits in the mix. - Roth, H.; Wernet, M.F. (Current Biology, 2021)
The molecular genetic dissection of Drosophila colour vision circuitry reveals converging pathways previously categorized as being chromatic versus achromatic. Amacrine-like Dm8 cells receive direct and indirect inputs with different spectral sensitivity tuning, thereby forming the second stage of colour-opponent processing.